ANALISIS SALURAN PEMASARAN DAN TINGKATAN PETANI ORGANIK DI KABUPATEN BOYOLALI - SUTARNO SUTARNO; SUSWADI SUSWADI (JURNAL ILMIAH AGRINECA, 2018)
Farmers' income level is generally influenced by many factors. Several factors related to the income level are the factors that come from the society itself, among others, from the socio-economic characteristics of the farmers themselves. Organic rice farming is one of the commodities that have bright prospects to increase farmers' income. This can motivate farmers to develop organic farming in the hope that the harvest will get high yields. The dangers posed by modern agricultural farming systems to health and the environment lead to increased public demand for organic products. The objectives of this research are: (1) The purpose of this research is to know and analyze the characteristics of farmers, (2) to analyze the total cost and income and income of organic rice, (3) to analyze the efficiency level and BEP (Break Even Point) certified organic rice farming. The sampling method used in this research is simple random sampling with 40 farmers calculated by Slovin formula. The analysis used are: (1) Average Scale Analysis for farmer characteristics (2) method of cost analysis and income and farm income, and (3) Analysis of farm efficiency using R / C (Return Cost Ratio) analysis method. The location of research is determined by purposive that is Dlingo Village, District Mojosongo, Boyolali District. The results of this study conclude that: (1) Characteristics of organic farmers play a role more than women, ages of organic farming above 50 years, Most farmers in Dlingo village have lived for more than 30 years, the main livelihood farmers are men. agricultural sector. (2) Based on the total average total cost for organic farming from certified group on average Rp.20.495.000, - Average income Rp. 35.000.000, -. Revenue per planting season is Rp. 14505.000, -. The organic certified farmer group earns a R / C ratio of 1.7, indicating that R / C> 1, then the farm with a certified organic system is efficient. Rice farm with certified organic system is advantageous because BEP value of production volume is 2,927 <farmer production, while BEP value is production price 4,099 <selling price at farmer level.Keywords: Characteristics, Organic farming, income, efficiency